DETECTION OF PHYTOCHEMICAL CONSTITUENT IN FLOWERS OF VIOLA ODORATA BY GAS CHROMATOGRAPHY-MASS SPECTROMETRY - Jasim, Shaimaa Fakhri; Baqer, Noor Nihad; Alraheem, Esam Abd (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Viola odorata has a characteristic as antifungal, antibacterial, anticancer, antioxidant, antiasthmatic, anti-inflammatory, anti-HIV, and antipyretic agents. The aim of this study was detected about bioactive compounds in the methanolic extract of V. odorata. Methods: The methanolic extract was analyzed through gas chromatography-mass spectrometry (GC-MS) for the identification of different compounds. Results: The current study investigated about phytochemicals in flowers of V. odorata. GC-MS analysis of the methanol extract of flowers showed 84 compounds. The highest concentration was for components which include ethanol, 2-(9,12-octadecadienyl oxy) -, (Z,Z)-; pentadecanoic acid; 1-pentacosanol; 1-pentacosanol; 2-furan carboxaldehyde, 5-(hydroxymethyl)-; 1,2 benzenedicarboxylic acid, diisooctyl ester; and docosane, 11-butyl- and gamma-sitosterol. The peak area and retention time for each components, respectively, were (15.709, 25.51%), (14.015, 19.51%), (29.914, 4.69%), (27.292, 3.95%), (5.707, 4.05%), (20.357, 3.91%), (18.289, 2.48%), and (30.431, 2.37%). While the others components ranged the peak area from 2.03% to 0.05%. Conclusions: These results indicate that the flowers of V. odorata contain the numerous components which have medical importance and this study was one of the first studies to detect phytochemicals in V. odorata.